BUDAYA PESANTREN DAN PENDIDIKAN KARAKTER PADA PESANTREN SALAF (Studi Kausus di Pondok Pesantren Al Munawwar ZarnujiyyahTasikmalaya) - Mumu (HASBUNA : Jurnal Pendidikan Islam, 2024)
The purpose of this research is basically to find out the culture or culture of the pesantren and character education in the salaf pesantren, Al-Munawwar Zarnujiyyah Tasikmalaya, precisely in Kampung Pasirbokor RT 05/01 Cipawitra Village, Mangkubumi District, Tasikmalaya City. The research method used in this research is descriptive method. The type of data in this study consists of primary data, and secondary data collected and processed by researchers through the interview method. Pesantren is one of the unique institutions with very strong and distinctive characteristics. The role taken is the efforts to educate the nation that have been passed down from generation to generation without stopping. Pesantren Al Munawwar Zarnujiyyah has a culture in shaping character and discipline that has been made in special rules as a habit in everyday life. One example of the santri culture in Pesantren Al Munawwar Zarnujiyyah is a culture of togetherness, queuing culture, mutual cooperation culture and other activities. The results of this study show: first, Pesantren Al Munawwar Zarnujiyyah has a strong role in the implementation of pesantren culture where the pesantren leadership has made rules and regulations in the form of SOP (Standard Operational Procedure), daily, weekly and monthly schedules. Second, the role of pesantren in Supporting the Success of Character Education of santri in the environment of Pesantren Al Munawwar Zarnujiyyah Tasikmalaya is carried out by transforming Islamic religious values with the process of instilling habits